Vitamin A deficiency triggers colonic methylation potentially impairing colonic neuron via downregulation SGK1/FOXO pathway - Bei Tong; Junyan Yan; Zhujun Sun; Ruifang Luo; Fang Lin; Riqiang Hu; Ting Yang; Yuting Wang; Jie Chen (Pediatric Discovery)
Abstract DNA methylation is widely involved in the modification of intestinal function, but the methylation mechanism in the enteric nervous system has not been studied in vitamin A deficiency (VAD). Herein, we firstly found that in the VAD group, gastrointestinal transit time was delayed compared with the vitamin A normal (VAN) group. RNA sequencing between VAD and VAN rats identified enriched pathways associated with enteric nerves and methylation transferase complexes. Then expression levels of DNA methyltransferases (DNMT1, DNMT3a and DNMT3b) were validated to significant increase in the VAD group. Representative reduced bisulfate sequencing showed that the VAD rats had high levels of DNA methylation in promoters and exons compared with the VAN rats. A combined methylomic and transcriptomic analysis identified that methylation levels of Sgk1, a key gene associated with enteric neural development, were elevated in the VAD group, and the activity of the SGK1/FOXO signaling axis was reduced. Furthermore, the colonic neuronal morphology and synaptic architecture were impaired in the VAD offspring. Interestingly, the above alterations in the VAD group were alleviated by vitamin A (VA) supplementation in the early postnatal period. These data suggest that VAD triggers colonic hypermethylation, which probably downregulates the SGK1/FOXO signaling pathway to cause colonic transfer dysfunction.